VD_FINDINFO Jug / 2015 / 62 vom 26. August 2014 - VD Tribunal cantonal (2014)
INDEMNITÉEN GÉNÉRAL, LOI FÉDÉRALE SUR LA CIRCULATION ROUTIÈRE, DILIGENCE, PASSAGE POUR PIÉTONS | 33 al. 2 LCR, 90 ch. 1 LCR, 429 CPP (CH)